Windfall Profits Under Pollution Permits and Output-Based Allocation - Zamorano-Ford, J (Springer Netherlands, 2018)
This paper analyzes the implementation of pollution permits. It focuses on the distributional impacts linked with the stringency of output-based allocation when two sectors are covered by the market for permits and the total cap is held constant. A new type of profit increase in sectors that are not exposed to international competition, when energy-intensive trade-exposed (EITE) sectors are granted output-based allocations, is demonstrated theoretically. The paper also illustrates a profit increase in the electricity sector in a possible fourth phase of the European Union Emission Trading Scheme, in which output-based allocation will be granted to EITE sectors, compared with the case in which all permits are auctioned. © 2016, Springer Science+Business Media Dordrecht.